2018
DOI: 10.1186/s12955-018-0977-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross cultural adaptation and analysis of psychometric properties of Sinhala version of Menopause Rating Scale

Abstract: BackgroundMenopause Rating Scale (MRS) evaluates eleven menopausal symptoms and health related quality of life (HRQOL) of postmenopausal women under three subscales. In this study we attempted cross cultural adaptation and evaluation of psychometric properties of a Sinhala translation of MRS.MethodsSinhala version of MRS was adapted following standard methodology; forward and backward translations, review by an expert group, focus group discussion (FGD) and pre-testing. It was self-administered among randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 16 publications
12
12
0
Order By: Relevance
“…Persian MRS, and the EFA and CFA confirmed the sound psychometric properties of the Persian model. Consistent with other studies [13,14,21], the internal consistency and test-retest reliability of the Persian model were good. The demonstrated psychometric properties of the Persian model of the MRS indicate its potential for use as the preferred scale for the assessment of menopausal symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Persian MRS, and the EFA and CFA confirmed the sound psychometric properties of the Persian model. Consistent with other studies [13,14,21], the internal consistency and test-retest reliability of the Persian model were good. The demonstrated psychometric properties of the Persian model of the MRS indicate its potential for use as the preferred scale for the assessment of menopausal symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Probably due to cultural considerations, the Iranian women in our study consider sexual problems as psychological symptoms [20]. This nding is similar to a survey of menopausal symptoms among Sinhalese women [14] who believed that both physical exhaustion and mental exhaustion were psychological symptoms. In other validation studies, musculoskeletal problems were loaded in both somatic and urogenital subscales [21,22].…”
Section: Discussionsupporting
confidence: 84%
“…This study's goal was to evaluate the psychometric properties of the Persian model of the MRS. We concluded that the Persian MRS has sound psychometric properties and that the validity and reliability are consistent with previous MRS validation studies [12][13][14]. Similar to the original MRS, a three-factor structure was generated utilized.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…MRS assesses 11 menopausal symptoms and their severity categorized into three independent subscales (somato-vegetative symptoms, psychological symptoms and urogenital symptoms) [23]. Both HPLP-II [24] and MRS [25] have been validated locally.…”
Section: Evaluations Of Hpb and Menopausal Symptom Severitiesmentioning
confidence: 99%